2017
DOI: 10.12973/iji.2017.1038a
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Utilising the Concept Maps in Teaching History

Abstract: Teaching History is a tough and challenging task for teachers because most students consider History as a boring subject. Many studies indicate that students are not interested in learning History. This paper is based on a quasi-experimental study conducted to investigate the effects of utilizing the concept map method in the teaching of History in secondary schools. The researchers investigated whether the use of concept maps in the teaching of History helped the subjects from the experimental group to answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
3
17
0
2
Order By: Relevance
“…(6) also found that teaching through concept mapping is more effective than teaching through lecture cum discussion method. According to (7) utilization of the concept map method in teaching History was able to raise students' achievement significantly for multiple choice type questions.…”
Section: Major Findings and Discussionmentioning
confidence: 99%
“…(6) also found that teaching through concept mapping is more effective than teaching through lecture cum discussion method. According to (7) utilization of the concept map method in teaching History was able to raise students' achievement significantly for multiple choice type questions.…”
Section: Major Findings and Discussionmentioning
confidence: 99%
“…Previous studies of concept maps have used tests consisting of either multiple‐choice questions or a combination of both multiple‐choice and constructed‐response questions to investigate their effect on students’ performance (Horton et al., 1993; Kaddoura et al., 2016; Nair & Narayanasamy, 2017; Witmer, 2015). We used a pretest and a posttest (see Appendix A) designed to measure students’ learning in OM.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated that well‐designed comprehensive concept maps, if used properly, may improve students’ understanding in a variety of subjects. Most of these studies relate to teaching courses in the sciences (Nair & Narayanasamy, 2017). The use of concept maps is championed as a metacognition strategy for implementing the theory of meaningful learning (Ausubel, 1963), that is, as a study tool to be constructed by students.…”
Section: Introductionmentioning
confidence: 99%
“…History offers the opportunity to control the future, as it shapes expectations for the future with information from the past (Torp, 2014;Crabtree, 2001;Taylor & Young, 2003). In addition, it has important roles such as developing awareness of citizenship, gaining sense of social belonging, and supporting identity development (Lorentzen, 2000;Fausser, 2000;Nair & Narayanasamy, 2017). On the other hand, this identity development contributes to being a good citizen by improving moral understanding (Stearns, 2009).…”
Section: Introductionmentioning
confidence: 99%